South Africa and the Korean War, the Politics of Involvement - Van der Waag-Cowling, N.M. (Scientia Militaria - South African Journal of Military Studies, 2017)
The Union of South Africa’s military involvement in the Korean War was an exercise in political maneuvering as opposed to one of any great military significance.[i] South Africa’s new right wing Nationalist Afrikaner government had, from 1948, embarked on a policy of legislating its racial policies, soon to be known as Apartheid. This new government primarily represented a people who were still deeply scarred by the Anglo Boer War. Many Afrikaners consequently wanted no part in any external conflicts that they viewed as Britain’s wars. South Africa’s foreign policy therefore became subject to an obvious and decisive shift away from that of the previous government under Jan Smuts, which had been broadly in line with that of Britain and the other Commonwealth dominions.[ii] The Korean War therefore presented the Nationalists with something of a dilemma. They did want to actively promote a stronger relationship with the United States but did not want to become involved in any military ventures with the British Commonwealth. Compounding this problem was the fact that the Nationalist government had identified the growing discontent of South Africa’s disenfranchised Black majority as her major security threat. The initial unwillingness of the South African government to commit anything tangible to the United Nations effort in Korea was therefore explicable. Geographically, Korea fell far outside of South Africa’s sphere of influence; furthermore this was a conflict which the Union could ill afford.[iii] South Africa had made massive financial sacrifices during the Second World War with contributions to the British war machine that were far beyond her actual reach and was very much still in the grip of post war austerity. Despite these factors combining to mitigate against South African involvement in Korea and the early isolationist stance of the Nationalist government regarding the Korean crisis, a noticeable and abrupt shift in subsequent policy some two months later bears witness to the theory that the Nationalist government underwent some sort of epiphany with a belated realization as to the potential benefits of military involvement for South Africa. These benefits included the desire of the South African government to be associated with the United States and be included in a formal regional treaty comparable to NATO together with the requirement for the acquisition of certain military hardware. These three aims have been postulated as the principle reason for this rather abrupt foreign policy deviation. This discussion will focus on providing some insight into how the South African government attempted to use the Korean War as a lever in order to attain these foreign policy objectives.